1973
DOI: 10.1111/j.1471-0528.1973.tb02190.x
|View full text |Cite
|
Sign up to set email alerts
|

A Scoring System for the Assessment of Multiple Methods of Monitoring Fetal Growth

Abstract: Forty-five "at risk" pregnancies were serially monitored by sonar biparietal cephalometry, 24-hour urinary oestriol assays and determination of serum oxytocinase, total alkaline phosphatase and heat-stable alkaline phosphatase activities. The results were assessed by a scoring system, and it was found that a combination of sonar cephalometry and 24-hour urinary oestriol assays gave the most reliable prediction of intrauterine growth retardation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1974
1974
1984
1984

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Several authors have found an association between birth-weight and matemal serum levels of hCS, estriol and oxytocinase [l, 8,10,11,12,14,15,16,17,18,20,21,22,23,25,28]. However, this association was not confirmed by others [4,6,7,19,27].…”
Section: Discussionmentioning
confidence: 44%
“…Several authors have found an association between birth-weight and matemal serum levels of hCS, estriol and oxytocinase [l, 8,10,11,12,14,15,16,17,18,20,21,22,23,25,28]. However, this association was not confirmed by others [4,6,7,19,27].…”
Section: Discussionmentioning
confidence: 44%
“…One hundred and eleven results from the 34 normal pregnancies were used to construct a normal range between 30 and 40 weeks of gestation. In common with other workers, we found that the normal values followed a lognormal distribution and transformation was effected as previously described (Robinson et al, 1973) before depicting the median values and 95 % confidence limits. …”
mentioning
confidence: 98%
“…The results were assessed by a scoring system, and it was found that a combination of sonar cephalometry and 24 h urinary oestriol assays gave the most reliable prediction of intrauterine growth retardation.In a previous communication, Robinson et al (1973) compared the value of five methods of fetal monitoring in respect of their ability to differentiate between normal and growth-retarded pregnancies in a small series of patients. These tests included sonar biparietal cephalometry, 24 h urinary oestriol assays and determination of serum oxytocinase, total alkaline phosphatase and heat-stable alkaline phosphatase activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some workers [17] consider an endocrine parameter to be not only normal or pathological but assign it a certain weight for estimating the risk, by evaluating its transverse position according to a point System, (e. g. estrogen excretion = low normal = l point, in dubious pathological r nge 2 points etc.). This leads to the following question: Is there a critical lower limit for estrogen excretion below which it is better to terminate pregnancy, i. e. for which chances for survival are better outside the uterus than within.…”
Section: Other Problems A) Critical Limit Of Hormone Excretionmentioning
confidence: 99%